Performance analysis of a biomass gasification based CCHP system with variable-effect LiBr-H2O absorption cooling and desiccant dehumidification. (February 2019) - Li, Xian; Kan, Xiang; Sun, Xiangyu; Zhao, Yao; Ge, Tianshu; Dai, Yanjun; Wang, Chi-Hwa
Abstract: A biomass gasification based combined cooling, heat and power (CCHP) system, with an internal combustion engine (ICE), a variable-effect LiBr-H2 O absorption chiller (VEAC), and a dehumidification air-conditioning with desiccant coated heat exchangers (DDAC), was evaluated for its performance in energy supply to a representative data center located in Singapore. The VEAC and DDAC were driven by the exhaust heat and jacket heat of the gas ICE, respectively. The operation strategy follows the electric load. Validated by experimental data, a 0-D code of the gasifier with Gibbs free energy minimization, an artificial neural network model of the VEAC, and a 1-D dynamic model of the DDAC, were built via considering reasonable deviation. In terms of the performance criterion, the energy supply and demand, and techno-economic of the system were evaluated. This work enables to contribute valuable data to the limited research on the biomass gasification-based CCHP application in Singapore's building sector.